Adaptive leadership and safety citizenship behaviors in Pakistan: the roles of readiness to change, psychosocial safety climate, and proactive personality - Khan, Hira Salah ud din; Chughtai, Muhmmmad Salman; Ma, Zhiqiang; Li, Mingxing; He, Di (Frontiers in Public Health, 2024)
Challenging times have put organizations in a perilous and chaotic state that demands immediate resolution and calls for effective leadership to navigate out of the crisis. In this context, we focused on psychosocial safety climate theory to investigate the influence of adaptive leadership on safety citizenship behaviors by looking at the mediating effect of readiness to change and moderating impact of psychosocial safety climate and proactive personality particularly in the Pakistani healthcare sector. To test the hypotheses, the data was collected from 397 employees working in the healthcare sector of Pakistan at two different times. The results of this study supported the model. The moderated path analysis revealed that psychosocial safety climate strengthens the direct effect of adaptive leadership on readiness to change, whereas the moderating impact of a proactive personality also strengthens the relationship between readiness to change and safety citizenship behaviors. Likewise, both moderators significantly moderated the indirect impact of adaptive leadership on safety citizenship behaviors via readiness to change. To conclude, the present study has significant implications for organizations and practitioners in both steady and uncertain environments.